Evaluation of Growth Hormone Results in Different Diagnosis and Trend Over 10 Year of Follow-up: A Single Center Experience - Zehra Aycan; Aslıhan Araslı Yılmaz; Servet Yel; Şenay Savaş Erdeve; Semra Çetinkaya (Galenos Yayincilik, 2021)
Objective:The aim was to evaluate the results of diagnosis, follow-up and treatment of the patients who recieved growth hormone (GH) treatment for the last 10 years and to determine the differences in the process and results over the years.Methods:Anthropometric, clinical, laboratory data, treatment adherence and side effects were evaluated retrospectively in 767 patients who recieved GH treatment between 2009-2018. Patients were grouped as isolated GH deficiency (IGHD), multiple pituitary hormone deficiency (MPHD), small for gestational age (SGA), and Turner syndrome (TS) depending on diagnosis.Results:GH treatment was started in 689 cases (89.8%) with IGHD, 24 (3.1%) with MPHD, 26 (3.4%) with SGA and 28 (3.7%) with TS. Median age of GH treatment onset was the earliest in SGA (8.4 years) and the latest in the IGHD group (12.0 years). At the time of treatment cessation, height standard deviation score (SDS) in IGHD and MPHD was significantly higher than treatment initiation time, whereas there was no significant difference in TS and SGA. One hundred eighty-nine cases reached the final height. Final heights for girls/boys were: IGHD 154/164.9 cm; MPHD 156.2/163.5 cm; TS 146.7 cm; and SGA 145.7/-cm, respectively. Target height SDS-final height SDS median values were IGHD: 0.1, MPHD: 0.6, SGA: 0.5, TS: 2.4 respectively. The patients' treatment compliance was high (92%) and the incidence of side effects was low (2.7%).Conclusion:In our cohort, GH treatment start age was late and no difference in this was observed in the last 10 years. The improvement in the height SDS was most marked in the IGHD and MPHD groups, the least in the TS and SGA groups.